The Crisis of Movement: Making and Remaking Global Supply Chains in Container Ports - Baumer Escobar, Vinzenz; Schober, Elisabeth; Sibilia, Elizabeth; Poulimenakos, Giorgos; Høyer Leivestad, Hege (Anthropologica, 2023)
The COVID-19 Pandemic issued a cascading crisis in the transport sector and has signified a wholesale reconfiguration of global supply chains. In studying supply chains, anthropological scholarship has tended to focus on tracking particular commodities as they move from producer to consumer. The central sites of circulation that enable this very movement of goods, however, remain understudied. Container ports in particular are key nodes where the thread of global supply chains gathers. A comparative ethnographic analysis of container ports is put forward in order to ground supply chains and logistics in particular socio-cultural histories, material infrastructures, political ecologies, and the politics of labour. We move from Singapore to Hamburg, through Algeciras up to Rotterdam and back down to Pireaus in order to show potential pathways to study the complex web of interconnections we refer to as the global supply chain, with a specific focus on labour and chokepoints in relation to multi-sited and scaled disruptions.